Factors Associated With The Utilization of Healthcare Facility Among The Ederly in X Hospital Semarang (Universitas Negeri Semarang, 2021)
Recently, the percentage of older adults in Semarang has increased significantly because of the success of national development in the field of health and welfare. Elderly people tend to have greater healthcare utilization because of their health status. However, we need to know the factors that influence the elderly in utilizing health services in X 65%hospitals in the framework of developing a geriatric clinic for improving elderly health services in Semarang. This study aimed to identify factors related to the use of outpatient services among the X Hospital elderly. This is cross sectional study using data from X Hospital, conducted in Januari- Maret 2020 Only those who were 60 years or older were included in the analyses. We used a logistic regression analysis to determine factors associated with use of outpatient services. Among 100 participants, 65% of respondents had actived using the outpatient services in X Hospital. Factors associated with the use of outpatient services were family income, knowledge, attitude of health worker, hospital facilities, self-rated health, the number of chronic conditions, and Activities of Daily Living (ADL).The need for elderly patients in outpatient services is likely to increase along with the increasing elderly population in Indonesia in general and in the City of Semarang in particular. Elderly activeness in Hospital X in utilizing health services in Hospital X provides an opportunity for hospitals in the development of geriatric clinics and service which are currently being initiated by hospitals. Geriatric services at X Hospital providing services to elderly patients to improve the quality of their health, both psychologically and physically., and facilitate them to access appropriate health services according to their needs